Clock-modulated checkpoints in time-restricted eating. Issue 1 (January 2022) - Li, Min-Dian
Abstract : Time-restricted eating (TRE), which limits the daily meal timing to a window of 6–12 h, has been shown to reduce the risks of cardiometabolic diseases through consolidating circadian rhythms of metabolism and physiology. Recent advances indicate that canonical circadian clocks are dispensable for the actions of TRE in the liver, and that meal timing entrains circadian rhythms in peripheral tissues in a tissue-specific manner (e.g., the liver and fat are readily entrainable, whereas the heart and kidneys are resistant). Here, we propose that TRE engages clock-modulated checkpoints (CCPs) to reset circadian rhythms of tissue functions. Elucidation of CCPs would reveal the mechanistic basis of tissue responsiveness to TRE, and facilitate the use of TRE in precision medicine for cardiometabolic diseases. Highlights: Time-restricted eating (TRE) is a regimen of intermittent fasting, and has the translational potential in the prevention and treatment of cardiometabolic diseases, including but not limited to obesity, metabolic dysfunction-associated fatty liver disease, and heart disease. However, it is unclear whether and how TRE regulates circadian rhythms in peripheral tissues. TRE regulates the peripheral clocks, transcriptomes, metabolomes, and physiology in a tissue-specific manner. The liver and adipose tissue are more responsive than the heart and kidneys to circadian regulation by TRE with respect to peripheral clocks and transcriptome. Clock-modulated checkpoints (CCPs) integrate signals from both the circadian clock and meal timing to maintain tissue homeostasis in peripheral tissues. TRE can bypass peripheral clocks to drive circadian rhythms through CCPs. Nuclear receptors and transcription factors in the control of glucose and lipid metabolism are emerging as key CCPs in TRE.